Mechanomorphosis: Science, Management, and "Human Machinery" in Industrial Canada, 1900-45 - Comacchio, Cynthia (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1998)
Abstract By the early 20th century, the changes taking place in western industrial capitalist nations prompted an adaptive shift in the socioeconomic delineation of human bodies, and in scientific theories about how they worked and how they could be put to work. Just as the rising social sciences borrowed from medicine to convey images of social malaise, medicine increasingly appropriated an industrial vocabulary to conceptualize bodily health. Depicted variously as a machine, a motor, a factory in itself, the human body absorbed industrial symbolism. Modern industry demanded an intensification of labour that made bodily efficiency paramount. The corresponding definition of health also shifted, from emphasis on physical endurance, which could be secured by simple replacement of outworn workers, to optimum labour efficiency, which had to be actively instilled in all workers, present and future. Scientific management programs were easily integrated with regulatory medical notions concerning the human body and human nature, as science, medicine and technology combined forces to promote a machine ethic that equated modernity, progress, efficiency, and national health. This paper considers the relationship between changing conceptualizations of the human body, developing medical influence and state regulation of health, and attempts to "Taylorize" the labour process in early 20th century Canada.